2004
DOI: 10.1038/sj.onc.1208095
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide induces autophagic cell death in malignant glioma cells by upregulation of mitochondrial cell death protein BNIP3

Abstract: Arsenic trioxide (As 2 O 3 ) has shown considerable efficacy in treating hematological malignancies with induction of programmed cell death (PCD) type I, apoptosis. However, the mechanisms underlying the antitumor effect of As 2 O 3 on solid tumors are poorly defined. Previously, we reported that As 2 O 3 induced autophagic cell death (PCD type II) but not apoptosis in human malignant glioma cell lines. The purpose of this study was to elucidate the molecular pathway leading to autophagic cell death. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
283
1
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 378 publications
(302 citation statements)
references
References 53 publications
9
283
1
9
Order By: Relevance
“…We observed that autophagy was enhanced by etoposide. The upregulation of autophagy by chemotherapeutic drugs has already been described [42][43][44][45][46][47]. Chemotherapyinduced autophagy may promote cell resistance against it.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We observed that autophagy was enhanced by etoposide. The upregulation of autophagy by chemotherapeutic drugs has already been described [42][43][44][45][46][47]. Chemotherapyinduced autophagy may promote cell resistance against it.…”
Section: Discussionmentioning
confidence: 93%
“…Many studies have reported that BNIP3 expression induces cell death with features that are both consistent and inconsistent with apoptosis suggesting that BNIP3 induces cell death through multiple pathways including apoptosis, necrosis and autophagy according to cell lines and conditions [13][14][15]44]. Indeed, BNIP3-induced cell death is related to mitochondrial dysfunction, membrane depolarization, permeability transition pore opening and increased generation of ROS according to the experimental conditions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…GFP-LC3-expressing cells have been successfully used to demonstrate induction of autophagy by amino-acid deprivation or anticancer treatments (Kabeya et al, 2000;Mizushima et al, 2001;Kanzawa et al, 2005). GFP-LC3 cells present a diffuse distribution under control conditions, whereas a punctate pattern of GFP-LC3 expression (GFP-LC3 dots) is induced by autophagy.…”
Section: Assessment Of the Involvement Of Lc3mentioning
confidence: 99%
“…GFP-LC3 cells present a diffuse distribution under control conditions, whereas a punctate pattern of GFP-LC3 expression (GFP-LC3 dots) is induced by autophagy. In the current study, we determined the prevalence of autophagic cells (i.e., cells expressing GFP-LC3 dots) by using the GFP-LC3 expression vector kindly provided by Dr Noboru Mizushima (Tokyo Metropolitan Institute of Medical Science, Tokyo, Japan), as described previously (Daido et al, 2005;Kanzawa et al, 2005). Tumor cells were transiently transfected with this vector by using Fugene 6 transfection reagent (Roche).…”
Section: Assessment Of the Involvement Of Lc3mentioning
confidence: 99%